Facebook and the Intricacies of Migrant Self-Making among Ilonggo OFWs in South Korea - Camposano, Clement C. (2018)
This article explores the diverse ways that Ilonggo-speaking male Filipino migrant workers in South Korea engage with Facebook. It studies the performance of online identities in relation to the migrants’ realities as social subjects and the technological mediation of the self and reciprocal exchange. It argues that online narratives can highlight facets of offline life that allow migrants a measure of biographical stability amid physical displacement, yet the same conditions create opportunities to negotiate competing online and offline narratives, complicating the illusion of a unified self. Online selves call for the need to reformulate Goffman’s notion of the interaction order.
Keywords: Social interaction; Parasocial interaction and relationships; Filipino foreign workers; Facebook (Web resource); Facebook (Electronic resource)--Social aspects; Goffman, Erving, 1922-1982